Peranan Audit Internal dalam Pencegahan (Fraud) Pada PT Bank Mandiri - Maulida Hasanah; Kasmanto Miharja; Tia Fahda Absyari; Rianyta Tanjung (BADAN PENERBIT STIEPARI PRESS, 2024)
The aim of this reseacrh is to analyze the role of internal audit in preventing fraud at PT Bank Mandiri using the Literature Review research method. Implementing a correct internal control system at PT Bank Mandiri can increase supervision of opportunities for fraud to occur, therefore the internal audit team has the quality to handle problems and carry out supervision well. SPAI-Standard no 120.2 2004 states that internal audit must have the knowledge and responsibility for understanding, investigating and testing for fraud. If internal audit has a good and correct monitoring function,opportunities for fraud to occur can be prevented.